Heterogeneous Pd/C-catalyzed, ligand free Suzuki–Miyaura coupling reaction furnishes new p-terphenyl derivatives. Issue 2 (17th January 2022) - Avula, Satya Kumar; Rehman, Najeeb Ur; Anwar, Muhammad U.; Aalthani, Ghanim; Csuk, Rene; Al-Harrasi, Ahmed
Abstract: A series of new para -terphenyls derivatives have been efficiently synthesized by a ligand-free heterogeneous Pd/C-catalyzed two-fold Suzuki–Miyaura coupling reaction. Methyl 5-bromo-2-iodobenzoate was selected to react with a variety of different aryl boronic acids (2a-i ). Nine new p -terphenyl derivatives (3a –i ) were prepared and the structures were confirmed by several analytical techniques including infrared, spectroscopy, 1 H and 13 C NMR spectroscopy, mass spectrometry, and in the case of compound 3 b, by X-ray diffraction method. The new derivatives were obtained in very good yields (78–91%). This synthetic facile route is envisioned to improve the preparation of p -terphenyl-based natural products. Abstract : UF0001